Deficiency of ASGR1 in pigs recapitulates reduced risk factor for cardiovascular disease in humans - Baocai Xie (Public Library of Science (PLoS), 2021)
Genetic variants in the asialoglycoprotein receptor 1 (ASGR1) are associated with a reduced risk of cardiovascular disease (CVD) in humans. However, the underlying molecular mechanism remains elusive. Given the cardiovascular similarities between pigs and humans, we generated ASGR1-deficient pigs using the CRISPR/Cas9 system. These pigs show age-dependent low levels of non-HDL-C under standard diet. When received an atherogenic diet for 6 months, ASGR1-deficient pigs show lower levels of non-HDL-C and less atherosclerotic lesions than that of controls. Furthermore, by analysis of hepatic transcriptome and in vivo cholesterol metabolism, we show that ASGR1 deficiency reduces hepatic de novo cholesterol synthesis by downregulating 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), and increases cholesterol clearance by upregulating the hepatic low-density lipoprotein receptor (LDLR), which together contribute to the low levels of non-HDL-C. Despite the cardioprotective effect, we unexpectedly observed mild to moderate hepatic injury in ASGR1-deficient pigs, which has not been documented in humans with ASGR1 variants. Thus, targeting ASGR1 might be an effective strategy to reduce hypercholesterolemia and atherosclerosis, whereas further clinical evidence is required to assess its hepatic impact. Author summary Previous studies have reported an association between ASGR1 variants and CVD in humans. However, the underlying mechanism is unknown. We used ASGR1-deficient pig to recapitulate the reduced risk features of CVD in humans with ASGR1 variants, indicating that ASGR1 inhibition could be an effective strategy to treat atherosclerotic CVD. Our results highlight the demand for taking advantage of genetically modified large animal models to investigate the pathogenesis and therapeutic development of CVD in humans. Unexpectedly, we demonstrate the first link between ASGR1 deficiency and liver injury, a feature that has not been documented in humans with ASGR1 variants. These results suggest that ASGR1 might be an effective target for reducing CVD, whereas revealing a genetic predisposition to liver disease in humans with ASGR1 variants.